Optimum biosurfactant production from sludge palm oil using klebsiella pneumoniae - Wan Mohd Fazli Wan Nawawi (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
This study introduces sludge palm oil (SPO) as a novel substrate for biosurfactant production by liquid state fermentation. Twenty one microorganisms were isolated from various hydrocarbon-based sources at palm oil mill and screened for biosurfactant production with the help of drop collapse method and surface tension activity. Klebsiella pneumoniae WMF02 was identified as most promising biosurfactant producer after strain screening. Plackett-Burman experimental design was employed to determine the important nutritional requirement for biosurfactant production by the selected strain under controlled conditions. Six out of eleven factors of the production medium were found to contribute significantly towards biosurfactant production, namely, sucrose, glucose, NaNO3, FeSO4, MgSO4, and K2HPO4. Sucrose was selected as co-substrate throughout the study based on comparison results between sucrose and glucose. Media optimization was carried in two stages. Initially, critical factor obtained from Plackett-Burman screening were subjected to one-factorat- a-time (OFAT) optimization in order to find the approximate central value of each nutrient that gave maximum biosurfactant production. In the second stage, face centered central composite design (FCCCD) was selected to further optimize the nutritional requirements (SPO, sucrose, K2HPO4, and MgSO4) while fixing FeSO4 and NaNO3 concentration at 0.3g/l and 2g/l respectively. Optimal concentration of nutrient were found at (g/l): Sucrose (2), MgSO4 (0.2), FeSO4 (0.3), NaNO3 (2), K2HPO4 (7), and SPO (85). Media optimization greatly reduced the surface tension of nonoptimized control from 36.2 mN/m to 27 mN/m (CMD-1 = 30mN/m and yield 85 g/l biosurfactant) as in optimized medium. Process optimization was also carried out in two stages using optimized media composition obtained previously. OFAT optimization for inoculum size and temperature was done in shake flask experiments gave the optimal value of 6% (v/v) and 370C respectively. OFAT optimization of aeration, agitation, and pH was carried out in bioreactor giving optimal value of 2.2 vvm, 300 rpm, and pH 8 respectively. This value was used to determine the minimum and maximum setting in later optimization. In second stage, aeration, agitation and pH were optimized using 3k-1 factorial design while fixing inoculum size and temperature at 6% (v/v) and 370C respectively. Optimum biosurfactant production in term of CMD-1 reduction was found at 1.8 vvm aeration, 314 rpm agitation speed, and pH 8.6 which gave CMD-1 reduction of 30.32 mN/m and 82.5 g/l biosurfactant yield. Scale up conversion from shake flask to bioreactor is not a straightforward matter, which need to be studied separately. Thus, similarity of results obtained in process optimization and media optimization is acceptable. Validation study of predicted response in optimization study gave a percentage difference of less than 10%, which indicated that the developed model can be used for further scale up study. The kinetic study revealed that the biosurfactant produced was growth associated and preliminary identification of crude extract indicated that the biosurfactant produced was phospholipid.